6=30-6x

Simple and best practice solution for 6=30-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=30-6x equation:


Simplifying
6 = 30 + -6x

Solving
6 = 30 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
6 + 6x = 30 + -6x + 6x

Combine like terms: -6x + 6x = 0
6 + 6x = 30 + 0
6 + 6x = 30

Add '-6' to each side of the equation.
6 + -6 + 6x = 30 + -6

Combine like terms: 6 + -6 = 0
0 + 6x = 30 + -6
6x = 30 + -6

Combine like terms: 30 + -6 = 24
6x = 24

Divide each side by '6'.
x = 4

Simplifying
x = 4

See similar equations:

| 3a+7a-4a= | | 2(a-8)=80 | | 26=4a-22 | | 12a-25=35 | | 4(3x-1)-2x=56 | | 50=7a-6 | | 7x+1250=1264 | | 21+9a=66 | | 3e^-(t/0.48) | | 236x-1888=0 | | x+(x+30500)=190500 | | 5-(3x)=0 | | 5-(3-x)=5 | | 2(x+5)+8= | | 4(3+h)-2(5+3h)= | | -3(y/1)= | | 27x^2+42x-9=0 | | ln(7-x)-ln(3x-1)=1 | | 35-3x=7-10x | | 3/9x | | 4x+9=31-6x | | 6x+-1(-x)=3x+8 | | 4x*5y*2z= | | ln(x+1)+lnx=2 | | 6k+1+5k= | | (3ad/4cd)^-2 | | 2+9x=4x-13 | | x+y+3xy=2015 | | 4a-9b= | | 4z/9-2=0 | | 7x+10y=300 | | (1-w)(5w-6)=0 |

Equations solver categories